The relationship between official development assistance and human development :|an empirical study on Sub-Saharan Africa - Dede, Mustafa Yunus. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2021., 2021)
Every year, billions of dollars are being spent in the form of the official development assistance by donor countries and multilateral institutions, to underpin the development process of the Sub-Saharan Africa region. Although these significant amounts of aid flows, current level of human development in the region is not exhibiting a bright picture. Sub-Saharan Africa still stands out as one of the geographies on which the people are suffering from extreme poverty, drought, and hunger the most. This thesis aims to gauge the impact of foreign aids on human development levels of Sub-Saharan African countries and to measure the effectiveness of aid in this way. To this end, panel data of 35 Sub-Saharan African countries spanning 2000-2017 period have been analyzed. Three different models have been established, and estimated utilizing general feasible generalized least squares (FGLS) technique. Across all model specifications, aid was found to have a negative impact on the human development level of the region. The potential reasons behind the negative impact were questioned through the control variables, and the developmental impacts of the initial level of human development, initial level of income, urbanization, investments, existing technological infrastructure, access to drinking water, access to sanitation services, the level of democratization and institutional quality were found out to be positive. Whereas industrialization and malaria prevalence had negative impacts on human development.
Keywords: Economic assistance -- Africa, Sub-Saharan.; Economic assistance -- Moral and ethical aspects.